A Bessel differential heat initial value problem in a reproducing kernel Hilbert space framework - Castro, L.P. (2017)
For modified Bessel heat equations subjected to an initial condition, we investigate integral transforms with kernels related to the solutions of those equations by using the theory of reproducing kernels. In particular, a new framework within reproducing kernel Hilbert spaces is proposed where we construct the unique solutions of the corresponding initial value problems.